S硬化性組成物及び硬化物

The curing composition with controlled thermal conductivity filler sizes and ratios, along with monomers and dispersants, addresses oil separation and viscosity issues in TIMs, ensuring stable thermal conductivity and application uniformity.

JP7625686B2Active Publication Date: 2025-02-03COSMO OIL LUBRICANTS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023510541
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-31
Filing Date
2022-01-26
Publication Date
2025-02-03
Estimated Expiration
2042-01-26

AI Technical Summary

Technical Problem

Existing curing compositions for thermal interface materials (TIMs) face issues with oil separation and sedimentation of thermal conductivity fillers, leading to compromised viscosity and thermal conductivity during storage and application.

Method used

A curing composition comprising specific particle size distributions of thermal conductivity fillers (A, B, and C) with controlled mass content ratios, along with monomers, polymerization initiators, and dispersants, enhances resistance to oil separation and maintains uniformity and thermal conductivity.

Benefits of technology

The composition achieves excellent resistance to oil separation, maintains viscosity stability, and ensures high thermal conductivity, making it suitable for gap fillers in electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625686000001
    Figure 0007625686000001
  • Figure 0007625686000002
    Figure 0007625686000002
  • Figure 0007625686000003
    Figure 0007625686000003
Patent Text Reader

Abstract

Provided are: a curable composition containing a heat-conductive filler (A), including at least one selected from the group consisting of heat-conductive fillers A having a volume average particle size of 0.3 μm to less than 1 μm and heat-conductive fillers B having a volume average particle size of 1 μm to less than 10 μm, and a heat-conductive filler C having a volume average particle size of 10-15 μm (inclusive), a monomer (B) having a (meth)acryloyl group, a polymerization initiator (C), and a dispersant (D), based on the total mass of the heat-conductive filler (A), the content X of the heat-conductive filler A being 0-40 mass%, the content Y of the heat-conductive filler B being 0-40 mass%, and the content Z of the heat-conductive filler C being 20-60 mass% (where, content X and content Y are not both 0 mass%); and a cured product thereof.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to curable compositions and cured products. [Background technology]

[0002] In recent years, the performance of electronic devices such as personal computers, mobile phones, and personal digital assistants (PDAs), and lighting and display devices such as light emitting diodes (LEDs) and electronic luminescent devices (ELs) has improved significantly, which is due to the remarkable improvement in the performance of computing elements and light emitting elements. As the performance of computing elements and light emitting elements improves, the amount of heat generated also increases significantly, and how to dissipate heat in electronic devices, lighting, and display devices has become an important issue. As a heat countermeasure, measures have been taken to provide TIM (Thermal Interface Materials; thermally conductive materials) between the heating element and the heat sink in order to transfer the heat generated by the computing elements or light emitting elements to the heat sink without loss and dissipate the heat through the heat sink. Heat dissipation sheets, thermally conductive greases, gap fillers, etc. are known as commonly used TIMs, and gap fillers, which are initially in a paste form and harden into a solid after application, have attracted attention.

[0003] As an example of a gap filler having excellent flexibility, shape stability, and thermal conductivity, International Publication No. 2020 / 149193 discloses a curable composition containing a compound (A) having one (meth)acrylate group in one molecule, a compound (B) having two or more (meth)acrylate groups in one molecule, a polymerization initiator (C), a dispersant (D), and a thermally conductive filler (E) containing zinc oxide. Summary of the Invention [Problem to be solved by the invention]

[0004] An object of one embodiment of the present disclosure is to provide a curable composition having excellent oil separation resistance. Another problem to be solved by another embodiment of the present disclosure is to provide a cured product of a curable composition that has excellent oil separation resistance. Here, in the present disclosure, "oil separation resistance" means that when the uncured curable composition according to the present disclosure is allowed to age, separation between the thermally conductive filler and a liquid component contained in the curable composition is suppressed. [Means for solving the problem]

[0005] The present disclosure includes the following embodiments. <1> A thermally conductive filler (A) including at least one selected from the group consisting of a thermally conductive filler A having a volume average particle diameter of 0.3 μm or more and less than 1 μm and a thermally conductive filler B having a volume average particle diameter of 1 μm or more and less than 10 μm, and a thermally conductive filler C having a volume average particle diameter of 10 μm or more and 15 μm or less; A monomer (B) having a (meth)acryloyl group; A polymerization initiator (C); A dispersant (D), Based on the total mass of the thermally conductive filler (A), the content X of the thermally conductive filler A is 0% by mass to 40% by mass, the content Y of the thermally conductive filler B is 0% by mass to 40% by mass, and the content Z of the thermally conductive filler C is 20% by mass to 60% by mass (however, both the content X and the content Y are not 0% by mass); Curable composition.

[0006] <2> The thermally conductive filler (A) contains at least one selected from zinc oxide, magnesium oxide, and aluminum oxide. <1> The curable composition according to claim 1. <3> The thermally conductive filler (A) contains zinc oxide. <2> The curable composition according to claim 1. <4> The thermally conductive filler (A) is a surface-treated thermally conductive filler. <1> ~ <3> 13. The curable composition according to claim 12,

[0007] <5> The monomer (B) contains a compound represented by the following formula (1): <1> ~ <4> 13. The curable composition according to claim 12,

[0008] [ka]

[0009] In formula (1), R 1 represents an alkyl group having 1 to 50 carbon atoms, R 2 represents a hydrogen atom or a methyl group.

[0010] <6> The monomer (B) contains a compound represented by the following formula (2): <1> ~ <5> 13. The curable composition according to claim 12,

[0011] [ka]

[0012] In formula (2), R B1 represents an alkylene group having 1 to 5 carbon atoms, R B2 and R B3 each independently represents a hydrogen atom or a methyl group, and n represents an integer of 4 or greater.

[0013] <7> <1> ~ <6> 2. A cured product of the curable composition according to claim 1. Effect of the Invention

[0014] According to one embodiment of the present disclosure, a curable composition having excellent oil separation resistance is provided. According to another embodiment of the present disclosure, there is provided a cured product of the curable composition having excellent oil separation resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The curable composition and the cured product thereof according to the present disclosure will be described in detail below. In this disclosure, the term "to" used to indicate a range of values ​​indicates a range that includes the values ​​set forth as the upper and lower limits. In addition, when a unit is set forth only for the upper limit of a range of values ​​set forth as "to", this also means that the lower limit is set in the same unit. In the present disclosure, the content or amount of each component in a composition means, when multiple substances corresponding to each component are present in the composition, the total content or amount of the multiple substances present in the composition, unless otherwise specified. In the present disclosure, in which numerical ranges are described in stages, the upper or lower limit value described in a certain numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In the numerical ranges described in the present disclosure, the upper or lower limit value described in a certain numerical range may be replaced with a value shown in the examples.

[0016] In the present disclosure, "(meth)acrylic" is a term used as a concept that includes both acrylic and methacrylic, and "(meth)acryloyl" is a term used as a concept that includes both acryloyl and methacryloyl. In the present disclosure, "mass %" and "weight %" are synonymous, and "parts by mass" and "parts by weight" are synonymous. In the present disclosure, when a plurality of components are present in the composition, each component in the composition means the total amount of the corresponding plurality of substances present in the composition, unless otherwise specified. In the present disclosure, combinations of two or more preferred embodiments are more preferred embodiments. In this disclosure, "JIS" is used as an abbreviation for Japanese Industrial Standards.

[0017] (Curable composition) The curable composition according to the present disclosure contains at least one selected from the group consisting of a thermally conductive filler A having a volume average particle diameter of 0.3 μm or more and less than 1 μm and a thermally conductive filler B having a volume average particle diameter of 1 μm or more and less than 10 μm, and a thermally conductive filler C having a volume average particle diameter of 10 μm or more and 15 μm or less (A), a monomer (B) having a (meth)acryloyl group, a polymerization initiator (C), and a dispersant (D), and based on the total mass of the thermally conductive filler (A), the content X of the thermally conductive filler A is 0 mass% to 40 mass%, the content Y of the thermally conductive filler B is 0 mass% to 40 mass%, and the content Z of the thermally conductive filler C is 20 mass% to 60 mass%. However, both the content X and the content Y are not 0 mass%. When the curable composition according to the present disclosure has the above configuration, it has excellent oil separation resistance.

[0018] In the following, thermally conductive filler A having a volume average particle diameter of 0.3 μm or more and less than 1 μm, thermally conductive filler B having a volume average particle diameter of 1 μm or more and less than 10 μm, and thermally conductive filler C having a volume average particle diameter of 10 μm or more and 15 μm or less will be simply referred to as thermally conductive filler A, thermally conductive filler B, and thermally conductive filler C, respectively.

[0019] Curable compositions containing solid particles such as thermally conductive fillers are required to have oil separation resistance over time (e.g., during storage) from preparation to use. In curable compositions with poor oil separation resistance, the thermally conductive filler settles, making stirring necessary when used, and a concentration gradient of the thermally conductive filler occurs in a storage container (e.g., a syringe), which can prevent the desired viscosity or thermal conductivity from being obtained, resulting in loss of uniformity in the amount of application and quality stability.

[0020] In addition, when the thermally conductive filler contained in the curable composition contains a large amount of thermally conductive fillers with medium and large particle sizes (e.g., volume average particle size of 10 μm or more), the thermal conductivity increases, but the thermally conductive fillers tend to settle and the oil separation resistance deteriorates. When the content of the thermally conductive fillers with medium and large particle sizes is reduced, the oil separation resistance improves, but the thermal conductivity tends to decrease.

[0021] In contrast, the curable composition according to the present disclosure contains, as the thermally conductive filler (A), at least one selected from the group consisting of thermally conductive filler A and thermally conductive filler B, and thermally conductive filler C, and the content X of thermally conductive filler A, the content Y of thermally conductive filler B, and the content Z of thermally conductive filler C are within predetermined ranges, and is therefore presumed to have excellent oil separation resistance.

[0022] The curable composition according to the present disclosure can also have excellent thermal conductivity (specifically, 3 W / m K or more), which is presumably due to the inclusion of the thermally conductive filler (A) in the above-mentioned configuration, more specifically, the inclusion of the thermally conductive filler C in the content ratio Z.

[0023] Furthermore, the curable composition according to the present disclosure can have a viscosity appropriate for the application (for example, gap filler application), which is presumably due to the inclusion of the thermally conductive filler (A) in the above-mentioned configuration, more specifically, the inclusion of the thermally conductive fillers A and B in the content ratios Y and Z, respectively.

[0024] Hereinafter, each component of the curable composition according to the present disclosure will be described.

[0025] <Thermal conductive filler (A)> The curable composition according to the present disclosure contains a thermally conductive filler (A). The thermally conductive filler (A) includes at least one selected from the group consisting of a thermally conductive filler A having a volume average particle diameter of 0.3 μm or more and less than 1 μm and a thermally conductive filler B having a volume average particle diameter of 1 μm or more and less than 10 μm, and a thermally conductive filler C having a volume average particle diameter of 10 μm or more and 15 μm or less.

[0026] Thermally conductive filler A, thermally conductive filler B, and thermally conductive filler C may each be one type of thermally conductive filler having a predetermined volume average particle diameter, or two or more types of thermally conductive fillers having a predetermined volume average particle diameter.

[0027] The volume average particle size of the thermally conductive filler A is 0.3 μm or more and less than 1 μm, preferably 0.4 μm to 0.8 μm, from the viewpoint of oil separation resistance. The volume average particle size of the thermally conductive filler B is from 1 μm to less than 10 μm, preferably 3 μm to 6 μm, from the viewpoint of oil separation resistance. The volume average particle size of the thermally conductive filler C is from the viewpoints of oil separation resistance and thermal conductivity, from 10 μm to 15 μm, and preferably from 11 μm to 13 μm.

[0028] The volume average particle size of the thermally conductive filler is measured by a laser diffraction / scattering method in accordance with JIS Z 8825:2013 (corresponding international standard: ISO13320). Specifically, a laser diffraction / scattering particle size analyzer is used to measure the volume distribution of the thermally conductive filler particles in a sample containing the thermally conductive filler particles. Based on the measured value (volume distribution) thus obtained, the volume average particle size of the thermally conductive filler particles contained in the sample can be calculated. An example of a laser diffraction scattering type particle size measuring device that can be used is a nanoparticle size distribution measuring device (product name: SALD-7500nano) manufactured by Shimadzu Corporation.

[0029] Whether the curable composition contains a thermally conductive filler belonging to thermally conductive filler A, thermally conductive filler B, or thermally conductive filler C can be confirmed by a laser diffraction / scattering particle size analyzer. Specifically, this can be confirmed by the following method. Components other than the thermally conductive filler are removed from the curable composition to isolate the thermally conductive filler. A measurement sample prepared from the isolated thermally conductive filler is subjected to a volume distribution measurement using a laser diffraction / scattering particle size analyzer. Based on the measurement results, the presence or absence of filler particles present within the particle size range of thermally conductive filler A, thermally conductive filler B, or thermally conductive filler C is confirmed. Components other than the thermally conductive filler are removed by the following method.

[0030] -Removal of components other than thermally conductive filler- The curable composition is dissolved in a solvent that does not dissolve the thermally conductive filler, such as hexane, and then centrifuged. The above process is repeated three or more times to separate the thermally conductive filler from the other components. The obtained thermally conductive filler is dried in a thermostatic chamber at 150° C. for 90 minutes to remove the residual solvent.

[0031] When a catalog value for the volume average particle diameter of the thermally conductive filler can be confirmed, the catalog value is used.

[0032] The thermally conductive filler (A) may contain only one or both of the thermally conductive filler A and the thermally conductive filler B. From the viewpoint of oil separation resistance, it is preferable that the thermally conductive filler (A) contains both the thermally conductive filler A and the thermally conductive filler B.

[0033] The content X of the thermally conductive filler A, the content Y of the thermally conductive filler B, and the content Z of the thermally conductive filler C can be confirmed by calculating the contents of the thermally conductive filler A, the thermally conductive filler B, and the thermally conductive filler C based on the measurement results of the particle size distribution of the thermally conductive filler (A) obtained by a laser diffraction / scattering type particle size measuring device.

[0034] The content X of the thermally conductive filler A is 0 mass % to 40 mass %, preferably 20 mass % to 35 mass %, and more preferably 25 mass % to 30 mass %, based on the total mass of the thermally conductive filler (A).

[0035] The content Y of the thermally conductive filler B is 0 to 40 mass %, preferably 10 to 30 mass %, and more preferably 15 to 25 mass %, based on the total mass of the thermally conductive filler (A).

[0036] The content Z of the thermally conductive filler C is 20% by mass to 60% by mass based on the total mass of the thermally conductive filler (A). The content Z can be, for example, 40% by mass to 60% by mass.

[0037] When the thermally conductive filler (A) contains both a thermally conductive filler A and a thermally conductive filler B, from the viewpoint of oil separation resistance, the content ratio of the thermally conductive filler A to the thermally conductive filler B [A:B] is preferably 30:70 to 80:20, more preferably 50:50 to 70:30, and even more preferably 55:45 to 65:35, by mass.

[0038] The content ratio of thermally conductive filler A and thermally conductive filler B to thermally conductive filler C [(A+B):C] is preferably 40:60 to 60:40, and more preferably 45:55 to 55:45, on a mass basis, from the viewpoints of oil separation resistance and thermal conductivity.

[0039] The material of the thermally conductive filler (A) is not particularly limited, and examples thereof include zinc oxide, magnesium oxide, aluminum oxide, boron nitride, aluminum nitride, carbon, etc. From the viewpoints of oil separation resistance, insulating properties, high thermal conductivity, and a track record of use as a thermally conductive filler, it is preferable to include at least one selected from zinc oxide, magnesium oxide, and aluminum oxide, and zinc oxide is more preferable.

[0040] In one embodiment, from the viewpoint of oil separation resistance, the thermally conductive filler (A) preferably contains only thermally conductive fillers A, B, and C, and from the viewpoints of oil separation resistance, viscosity, and high thermal conductivity, it is more preferable that all of the thermally conductive fillers A, B, and C are zinc oxide.

[0041] The thermally conductive filler (A) may be a surface-treated thermally conductive filler. The surface-treated thermally conductive filler can improve the affinity with other components contained other than the thermally conductive filler, and can contribute to oil separation resistance, low viscosity, and improved thermal conductivity.

[0042] The surface treatment of the thermally conductive filler is not particularly limited and may be a physical treatment or a chemical treatment, and any known treatment capable of treating the surfaces of the particles constituting the thermally conductive filler can be applied. The surface treatment is preferably a treatment using a surface treatment agent.

[0043] Examples of the surface treatment agent include a silane-based coupling agent, a titanium-based coupling agent, a carboxylic acid-based coupling agent, a phosphoric acid-based coupling agent, a fatty acid, a polymer compound, a surfactant, and oils and fats.

[0044] From the viewpoint of dispersibility, the thermally conductive filler (A) is preferably surface-treated with a silane coupling agent as a surface treatment agent.

[0045] The thermally conductive fillers A, B, and C may all be surface-treated thermally conductive fillers, or any one of the thermally conductive fillers may be surface-treated. From the viewpoint of oil separation resistance and thermal conductivity, it is preferable that the thermally conductive filler C contains at least a surface-treated thermally conductive filler.

[0046] -Content- The content of the thermally conductive filler (A) is preferably 80 mass % or more, more preferably 85 mass % to 98 mass %, and even more preferably 90 mass % to 96 mass %, based on the total mass of the composition. The content of the thermally conductive filler (A) is preferably 40% by volume or more, more preferably 47% by volume to 80% by volume, and even more preferably 60% by volume to 80% by volume, based on the total volume of the composition. When the content of the thermally conductive filler (A) is within the above range, the oil separation resistance can be further improved.

[0047] <Monomer (B) Having a (Meth)acryloyl Group> The curable composition according to the present disclosure includes a monomer (B) having a (meth)acryloyl group. The monomer (B) having a (meth)acryloyl group may be a monomer having one (meth)acrylate group in one molecule, or may be a monomer having two or more (meth)acrylate groups in one molecule. The monomer having one (meth)acrylate group in one molecule is not particularly limited, and examples thereof include linear, branched or cyclic alkyl (meth)acrylates, acrylic acid and the like. From the viewpoint of achieving both heat resistance and flexibility, the monomer having one (meth)acrylate group in one molecule is preferably a linear or branched alkyl (meth)acrylate, and more preferably contains a compound represented by the following formula (1).

[0048] [ka]

[0049] In formula (1), R 1 represents an alkyl group having 1 to 50 carbon atoms, R 2 represents a hydrogen atom or a methyl group.

[0050] In formula (1), R 1The alkyl group in may be linear or branched, and may have a substituent. Examples of the substituent include a carboxy group, a hydroxy group, an amino group, an aryl group, and a heterocyclic group. A carboxy group or a hydroxy group is preferable, and a hydroxy group is more preferable.

[0051] From the viewpoint of achieving both heat resistance and flexibility, R 1 The alkyl group in the formula (I) preferably has 2 to 30 carbon atoms in total, more preferably 5 to 25 carbon atoms, further preferably 10 to 25 carbon atoms, and particularly preferably has 12 to 24 carbon atoms in total. Here, when the alkyl group has a substituent containing a carbon atom, the total number of carbon atoms means the total number of carbon atoms including the number of carbon atoms of the substituent.

[0052] From the viewpoint of achieving both heat resistance and flexibility, R 1 is preferably a linear or branched alkyl group or a substituted alkyl group having a total of 2 to 30 carbon atoms, more preferably a linear or branched alkyl group or a hydroxyl group-containing alkyl group having a total of 2 to 25 carbon atoms, and is preferably a linear or branched unsubstituted alkyl group having 12 to 24 carbon atoms.

[0053] Examples of monomers having one (meth)acrylate group in one molecule include lauryl (meth)acrylate, isostearyl (meth)acrylate, tetradecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, and 2-decyltetradecyl (meth)acrylate.

[0054] R 2 is a hydrogen atom or a methyl group, and is preferably a methyl group.

[0055] Examples of monomers having two or more (meth)acrylate groups in one molecule include hexanediol di(meth)acrylate, butanediol di(meth)acrylate (1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate), ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and trimethylolpropane tri(meth)acrylate.

[0056] From the viewpoint of achieving both heat resistance and flexibility, the monomer having two or more (meth)acrylate groups in one molecule is preferably a compound having two and / or three (meth)acrylate groups in one molecule, more preferably a compound having two (meth)acrylate groups in one molecule, and even more preferably a compound represented by the following formula (2).

[0057] [ka]

[0058] In formula (2), R B1 represents an alkylene group having 1 to 5 carbon atoms, R B2 and R B3 each independently represents a hydrogen atom or a methyl group, and n represents an integer of 4 or greater. R B1 The alkylene group having 1 to 5 carbon atoms represented by the following formula may be linear or branched. From a flexibility perspective, R B1The alkylene group represented by the formula (I) is preferably a linear or branched alkylene group having 2 to 5 carbon atoms, more preferably a linear or branched alkylene group having 2 to 4 carbon atoms, and even more preferably a branched alkylene group having 3 or 4 carbon atoms. R B2 and R B3 is preferably each independently a methyl group. n is preferably 4-25, more preferably 4-10, and further preferably 4-8.

[0059] From the viewpoint of flexibility and shape stability, R B1 is a linear or branched alkylene group having 2 to 5 carbon atoms (more preferably a linear or branched alkylene group having 2 to 4 carbon atoms, and even more preferably a branched alkylene group having 3 or 4 carbon atoms), R B2 and R B3 is a methyl group, and n is preferably 4 to 25 (more preferably 4 to 10, and further preferably 4 to 8).

[0060] The content of the monomer (B) having a (meth)acryloyl group is preferably from 1 to 10% by mass, and more preferably from 2 to 8% by mass, based on the total mass of the composition. The (meth)acryloyl group-containing monomer (B) may be contained in the composition either alone or in combination of two or more kinds.

[0061] In one embodiment, the monomer (B) having a (meth)acryloyl group preferably includes at least one selected from monomers having one (meth)acrylate group in one molecule, and at least one selected from monomers having two or more (meth)acrylate groups in one molecule.

[0062] The content ratio (A:B) of the content A of the monomer having one (meth)acrylate group in one molecule to the content B of the monomer having two or more (meth)acrylate groups in one molecule is preferably 99.5:0.5 to 95:5, and more preferably 99:1 to 97:3, on a mass basis, from the viewpoints of the hardness and curing rate of the cured product.

[0063] The monomer (B) having a (meth)acryloyl group is preferably a monomer having a molecular weight of less than 1,000. In this disclosure, a monomer refers to a polymerizable compound having a molecular weight of less than 1,000, and a polymerizable polymer refers to a polymerizable compound having a weight average molecular weight (Mw) of 1000 or more. The concept of "polymerizable polymer" in the present disclosure also includes so-called oligomers.

[0064] <Polymerization initiator (C)> The curable composition according to the present disclosure contains a polymerization initiator (C). The polymerization initiator (C) is a compound that generates polymerization initiating species such as radicals and cations by the energy of light, heat or both, and can be appropriately selected from known thermal polymerization initiators, known photopolymerization initiators, etc. As the polymerization initiator (C), from the viewpoint of the reactivity of the monomer (B) having a (meth)acryloyl group, a radical polymerization initiator is preferable, a peroxide that generates free radicals by heat is more preferable, and an organic peroxide that generates free radicals by heat is even more preferable.

[0065] The organic peroxides include isobutyl peroxide, α,α'-bis(neodecanoylperoxy)diisopropylbenzene, cumyl peroxyneodecanoate, di-n-propyl peroxydicarbonate, di-s-butyl peroxydicarbonate, 1,1,3,3-tetramethylbutyl peroxyneodecanoate, bis(4-t-butylcyclohexyl)peroxydicarbonate, 1-cyclohexyl-1-methylethyl peroxyneodecanoate, di-2-ethoxyethyl peroxydicarbonate, and di(ethylhexyl)peroxy. Dicarbonate, t-hexyl peroxyneodecanoate, dimethoxybutyl peroxydicarbonate, di(3-methyl-3-methoxybutyl) peroxydicarbonate, t-butyl peroxyneodecanoate, t-hexyl peroxypivalate, 3,5,5-trimethylhexanoyl peroxide, octanoyl peroxide, lauroyl peroxide, stearoyl peroxide, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, succinic peroxide, 2,5-dimethyl-2,5-di (2-ethylhexanoyl)hexane, 1-cyclohexyl-1-methylethylperoxy-2-ethylhexanoate, t-hexylperoxy-2-ethylhexanoate, 4-methylbenzoyl peroxide, t-butylperoxy-2-ethylhexanoate, m-toluenebenzoyl peroxide, benzoyl peroxide, t-butylperoxyisobutyrate, 1,1-bis(t-butylperoxy)2-methylcyclohexane, 1,1-bis(t-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1 -Bis(t-hexylperoxy)cyclohexane, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclohexanone, 2,2-bis(4,4-dibutylperoxycyclohexyl)propane, 1,1-bis(t-butylperoxy)cyclododecane, t-hexylperoxyisopropyl monocarbonate, t-butylperoxymaleic acid, t-butylperoxy-3,5,5-trimethylhexanoate, t-butylperoxylaurate, 2,5-dimethyl-2,5-di(m-toluoylperoxy)hexane, t-butylperoxyisopropyl monocarbonate, t-butylperoxy-2-ethylhexyl carbonate, t-hexylperoxybenzoate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, t-butylperoxyacetate, 2,2-bis(t-butylperoxy)butane, t-butylperoxybenzoate, n-butyl-4,4-bis(t-butylperoxy)valerate, di-t-butylperoxyisophthalate, α,α'-bis(t-butylperoxy)diisopropylbenzene, dicumylperoxy Examples of peroxides include 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, t-butylcumyl peroxide, di-t-butyl peroxide, p-menthane hydroperoxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexyne, diisopropylbenzene hydroperoxide, t-butyltrimethylsilyl peroxide, 1,1,3,3-tetramethylbutyl hydroperoxide, cumene hydroperoxide, t-hexyl hydroperoxide, t-butyl hydroperoxide, benzoyl peroxide, and lauroyl peroxide. Among these, from the viewpoint of reactivity, the organic peroxide is preferably at least one compound selected from the group consisting of benzoyl peroxide, t-butylperoxy-2-ethylhexyl carbonate, 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate, and cumene hydroperoxide.

[0066] -Content- The content of the polymerization initiator (C) is preferably 0.5 parts by mass or more and 10 parts by mass or less, and more preferably 0.5 parts by mass or more and 4 parts by mass or less, based on 100 parts by mass of the monomer (B) having a (meth)acryloyl group.

[0067] <Dispersant (D)> The curable composition according to the present disclosure comprises a dispersant (D). The dispersant is not particularly limited, and examples thereof include anionic surfactants, cationic surfactants, nonionic surfactants, amphoteric surfactants, polymeric surfactants, alcohols, compounds having a carboxy group such as fatty acids, metal soaps, fatty acid oligomer compounds, fluorine-based surfactants, and boron-based surfactants. The dispersant (D) is preferably at least one compound selected from the group consisting of nonionic surfactants, compounds having a carboxy group, and metal soaps.

[0068] Examples of nonionic surfactants include polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene sorbitol fatty acid esters, glycerin fatty acid esters, polyoxyethylene glycerin fatty acid esters, polyglycerin fatty acid esters, polyglycerin fatty acid ethers, polyglycerin monoalkyl ethers, sucrose fatty acid esters, polyoxyethylene alkylamines, polyethylene glycol polypropylene glycol block copolymers, acetylene glycol, and polyoxyethylene adducts of acetylene glycol.

[0069] The compound having a carboxyl group is not particularly limited, and may be a fatty acid having one carboxyl group and a hydrocarbon group in one molecule, or a compound having two or more carboxyl groups in one molecule. In an embodiment, as the dispersant (D), a compound having a carboxyl group is more preferable, and a fatty acid is even more preferable.

[0070] Examples of the compound having a carboxy group include aromatic carboxylic acids and fatty acids having an aliphatic hydrocarbon group having 12 to 22 carbon atoms. Examples of fatty acids having an aliphatic hydrocarbon group having 12 to 22 carbon atoms include stearic acid, oleic acid, palmitic acid, myristic acid, and lauric acid.

[0071] Examples of compounds having a carboxy group include polycarboxylic acids (i.e., polycarboxylic acids) having two or more carboxy groups in one molecule, such as oxalic acid, malonic acid, succinic acid, fumaric acid, maleic acid, and adipic acid; polycarboxylic acid salts such as alkylamine salts, alkylammonium salts, polyaminoamide polycarboxylates, sodium salts of polycarboxylates, ammonium salts of polycarboxylates, and aminoalcohol salts of polycarboxylates; and polycarboxylic acid copolymers.

[0072] Examples of the polycarboxylic acid compound include alkylamine salts, alkylammonium salts, polyaminoamide polycarboxylates, sodium salts of polycarboxylates, ammonium salts of polycarboxylates, and aminoalcohol salts of polycarboxylates.

[0073] Examples of the metallic soap include metal salts of higher fatty acids such as calcium stearate, potassium oleate, and calcium oleate.

[0074] From the viewpoint of flexibility, the dispersant (D) preferably contains at least one compound selected from the group consisting of a polyglycerol monoalkyl ether compound, a compound having a carboxy group, and a metal soap, more preferably contains at least one compound selected from the group consisting of a polyglycerol monoalkyl ether compound and a fatty acid having an aliphatic hydrocarbon group having 12 to 22 carbon atoms, and further preferably contains at least one compound selected from the group consisting of a polyglycerol monoalkyl ether compound and a fatty acid having an unsaturated hydrocarbon group having 18 to 22 carbon atoms.

[0075] -Content- The content of the dispersant (D) is preferably 0.1 parts by mass or more and 3 parts by mass or less, more preferably 0.1 parts by mass or more and 1 part by mass or less, and particularly preferably 0.2 parts by mass or more and 0.8 parts by mass or less, relative to 100 parts by mass of the thermally conductive filler (A).

[0076] <Plasticizer (E)> The curable composition according to the present disclosure preferably comprises a plasticizer (E). The plasticizer (E) is not particularly limited, and examples thereof include polymers used as plasticizers, fatty acid ester compounds having an unsaturated hydrocarbon group, aromatic carboxylic acid ester compounds, and oils containing fatty acids and aromatic carboxylic acids having an unsaturated hydrocarbon group. In this disclosure, "polymer" refers to a compound having a weight average molecular weight (Mw) of 1,000 or more. In the present disclosure, the concept of "polymer" also includes so-called oligomers.

[0077] Examples of the polymer include acrylic polymers, polyester polymers, polyurethane polymers, and silicone polymers, with acrylic polymers being preferred from the viewpoints of heat resistance and flexibility.

[0078] Examples of polymers used as plasticizers include acrylic polymers, polyester polymers, polyurethane polymers, and silicone polymers. From the viewpoints of heat resistance and flexibility, acrylic polymers are preferred.

[0079] From the viewpoint of heat resistance, the acrylic polymer preferably contains a structural unit formed from an acrylic ester. The (meth)acrylic ester is preferably an alkyl (meth)acrylate. Examples of the meth)acrylic ester include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, and isobutyl (meth)acrylate. The alkyl acrylate may be a non-functional alkyl acrylate, or may have a functional group such as a carboxy group or a hydroxy group (hydroxyl group). The functional group contained in the alkyl acrylate is preferably a hydroxy group.

[0080] The acrylic polymer is represented by the following formula (P ACThe polymer may have a structure represented by the formula:

[0081] [ka]

[0082] Formula (P AC ), R P represents a hydrogen atom or an alkyl group. Formula (P AC In the above, the alkyl group may have a substituent. Examples of the substituent include a carboxy group, a hydroxyl group, and an amino group. The substituent is preferably a carboxy group or a hydroxy group, and more preferably a hydroxy group. The alkyl group is preferably a saturated alkyl group, more preferably an alkyl group having 1 to 4 carbon atoms.

[0083] When the curable composition according to the present disclosure contains a plasticizer (E) and the plasticizer (E) is a polymer, from the viewpoints of heat resistance and flexibility, the plasticizer (E) is preferably a polymer having a glass transition temperature of -20°C or lower, and more preferably an acrylic polymer having a glass transition temperature of -20°C or lower. When the curable composition according to the present disclosure contains a plasticizer (E) and the plasticizer (E) is a polymer, from the viewpoints of heat resistance and flexibility, the plasticizer (E) is preferably a polymer having a glass transition temperature of -90°C or more and -20°C or less, and more preferably an acrylic polymer having a glass transition temperature of -90°C or more and -20°C or less. The glass transition temperature (Tg) of a polymer can be determined by examining the inflection point of a DSC curve measured using a differential scanning calorimeter (DSC).

[0084] Examples of fatty acid ester compounds having an unsaturated hydrocarbon group include ester compounds of palmitoleic acid, oleic acid, linoleic acid, linolenic acid, and the like. Examples of the aromatic carboxylate compound include ester compounds of phthalic acid, terephthalic acid, benzoic acid, trimellitic acid, and the like.

[0085] When the curable composition according to the present disclosure contains a plasticizer (E), from the viewpoint of high-temperature stability, the plasticizer (E) preferably contains an aromatic carboxylic acid ester compound, and more preferably contains a trimellitic acid ester.

[0086] -Content- When the curable composition according to the present disclosure contains a plasticizer (E) (the total amount when two or more types of plasticizers (E) are contained), from the viewpoint of achieving both heat resistance and flexibility, the content of the plasticizer (E) is preferably 10 parts by mass or more and 60 parts by mass or less, more preferably 20 parts by mass or more and 50 parts by mass or less, and even more preferably 30 parts by mass or more and 45 parts by mass or less, relative to 100 parts by mass of the monomer (B) having a (meth)acryloyl group. The plasticizer (E) may be contained in one type alone or in a combination of two or more types.

[0087] <Other additives>> The curable composition according to the present disclosure may contain components other than the thermally conductive filler (A), the compound (B) having a (meth)acryloyl group, the polymerization initiator (C), the dispersant (D), and the plasticizer (E) (hereinafter also referred to as “other additives”), as necessary. Other additives that may be appropriately blended include a reducing agent (F), an antioxidant, a corrosion inhibitor, a rust inhibitor, and a rheology control agent (viscosity modifier). The above additives may be used alone or in combination of two or more.

[0088] <<Reducing agent (F)>> The curable composition according to the present disclosure may contain a reducing agent (F) as necessary. When the curable composition according to the present disclosure is applied to a two-component curable composition described later, it is preferable that one of the compositions contains a reducing agent (F). By adding the reducing agent (F), the decomposition of the polymerization initiator (C) (e.g., peroxide) is easily promoted, and the polymerization reaction easily proceeds even under low temperature conditions.

[0089] The reducing agent (F) is not particularly limited as long as it can promote the decomposition of the polymerization initiator (C), and examples thereof include known reducing agents that are used in combination with polymerization initiators. From the viewpoint of promoting the decomposition of the polymerization initiator (C), a metal compound-based reducing agent is preferable.

[0090] Examples of metal compound reducing agents include stannous oxide, dioctyltin dilaurate, dibutyltin dilaurate, dibutyltin diacetate, zinc naphthenate, antimony trichloride, potassium oleate, sodium O-phenylphenate, bismuth nitrate, ferric chloride, tetra-n-butyltin, tetra(2-ethylhexyl) titanate, cobalt 2-ethylhexoate, and ferric 2-ethylhexoate.

[0091] -Content- When the curable composition according to the present disclosure contains a reducing agent (F), from the viewpoint of the curing rate, the content of the reducing agent (F) is preferably 0.5 parts by mass or more and 10 parts by mass or less, and more preferably 2 parts by mass or more and 9 parts by mass or less, relative to 100 parts by mass of the monomer (B) having a (meth)acryloyl group. The reducing agent (F) may be used alone or in combination of two or more kinds.

[0092] <<Antioxidants>> Examples of the antioxidant include phenol-based antioxidants, amine-based antioxidants, and phosphite-based antioxidants.

[0093] <<Corrosion inhibitor>> Corrosion inhibitors include benzotriazole, tolyltriazole, thiadiazole, benzimidazole, and the like.

[0094] <<Rust inhibitor>> Examples of the rust inhibitor include metal sulfonate compounds and sorbitan compounds.

[0095] <<Rheology control agent>> In the present disclosure, a rheology control agent refers to an additive that imparts non-Newtonian properties to changes in shear rate. Specifically, a rheology control agent is an additive that imparts flow characteristics such that the shear viscosity is high in the low shear rate range and low in the high shear rate range.

[0096] The rheology control agent may be an inorganic compound-based rheology control agent or an organic compound-based rheology control agent. Examples of inorganic compound-based rheology control agents include fumed silica, bentonite, mica, and kaolin. Examples of the organic compound-based rheology control agent include urea-modified polymers, urethane-modified polymers, castor oil wax, polyethylene wax, polyamide wax, and fatty acid amide wax. Among these, the rheology control agent is preferably an inorganic compound-based rheology control agent, more preferably fumed silica or bentonite, and even more preferably bentonite. When using fumed silica, it is preferable to use one whose surface is made hydrophobic by a silane coupling agent or other surface modifier. When using bentonite, it is preferable to use an organically modified bentonite that is organically modified by a quaternary ammonium salt or other organic modifier.

[0097] The content of the rheology control agent is not particularly limited and can be set appropriately.

[0098] [Physical Properties of Curable Composition] The spreading consistency of the curable composition according to the present disclosure is preferably 100 to 500, more preferably 260 to 340, and even more preferably 280 to 310, from the viewpoints of viscoelasticity, handleability, and defoaming properties. The spreading consistency is calculated by inserting 0.05 mL of a sample (curable composition before curing) between two acrylic plates in an environment of 25°C, compressing the sample by applying a load of 100 g on the plates for 5 seconds, measuring the spreading diameter of the sample in millimeters, subtracting 1 from this measurement and multiplying the result by 20. Spreading consistency = (measured value - 1) x 20

[0099] [Form of the curable composition] The curable composition according to the present disclosure is preferably a one-part curable composition in which one type of curable composition is used when applying to a substrate, a heating element, etc. The curable composition according to the present disclosure may be a two-part curable composition in which two types of curable compositions are mixed and used.

[0100] [Method for producing curable composition] The method for producing the curable composition according to the present disclosure is not particularly limited, and is not particularly limited. The curable composition according to the present disclosure can be produced, for example, by the following method. In an embodiment, the curable composition according to the present disclosure can be obtained by adding a thermally conductive filler (A), a polymerization initiator (C), and a dispersant (D), and optionally a plasticizer (F) and other additives, to a stirring vessel and stirring and mixing them. For stirring and mixing, a known stirrer or the like can be used.

[0101] In the method for producing a curable composition, when other additives are added, the composition may be stirred for a period of time sufficient for the additives to dissolve or disperse. The other additives may be added to the stirring vessel together with the components other than the other additives, or may be added to the stirring vessel after mixing the components other than the other additives.

[0102] (cured product) The cured product according to the present disclosure is a cured product of the curable composition according to the present disclosure. The method for curing the curable composition is not limited and can be appropriately selected from commonly used methods. The curing method includes irradiation with active energy rays, heating, etc., and the curing method by heating is preferred. When curing is performed by heating, the heating temperature is preferably 60° C. or higher, and more preferably 70° C. or higher. The heating time is preferably 1 minute to 120 minutes. The curable composition may be cured by reacting with moisture in the air, or may be cured at room temperature.

[0103] From the viewpoints of flexibility, shape stability, and suppression of changes in thermal conductivity, the thermal conductivity of the cured product according to the present disclosure is preferably from 0.5 [W / m·K] to 50 [W / m·K], preferably from 1 [W / m·K] to 20 [W / m·K], and more preferably from 3 [W / m·K] to 20 [W / m·K].

[0104] The softness of the cured product according to the present disclosure is preferably 100 or less, and more preferably 85 or less in Shore OO hardness, from the viewpoint of stress relaxation to peripheral parts of the cured product. Similarly, the Asker C hardness is preferably 100 or less, more preferably 85 or less, and even more preferably 75 or less. Regarding the softness of the cured product according to the present disclosure, Shore OO hardness is measured in accordance with ASTM D2240, and Asker C hardness is measured in accordance with JIS K 7312:1996.

[0105] <Application> The curable composition according to the present disclosure can be suitably used, for example, as a TIM that is filled in a recess (that is, a gap between a heat generating element and a heat sink) formed in a substrate. The curable composition according to the present disclosure has excellent oil separation resistance, and therefore can maintain the desired quality for a long period of time. In addition, the curable composition according to the present disclosure has excellent viscosity and thermal conductivity, and therefore the cured product obtained has excellent manufacturability and thermal conductivity. The cured product obtained from the curable composition according to the present disclosure has excellent flexibility, shape stability, and thermal conductivity, and therefore has excellent conformability to the coated surface such as a recess formed on a substrate, and therefore can efficiently release heat even when there are components of different heights on the substrate. In addition, the curable composition according to the present disclosure can efficiently release heat because it can conform to the microscopic unevenness of the material on the substrate, and also has excellent conformability to the coated surface due to temperature fluctuations, and therefore can be suitably used as a gap filler. EXAMPLES

[0106] The curable composition and the cured product according to the present disclosure will be specifically described below with reference to examples. Note that the curable composition and the cured product according to the present disclosure are not limited to these examples in any way.

[0107] (Examples 1 to 10 and Comparative Examples 1 to 6) The raw materials were mixed in the amounts shown in Table 1 or Table 2, and mixed at 2,000 rpm (revolutions per minute) for 2 minutes under atmospheric pressure using a planetary centrifugal mixer (Thinky Corporation, product name: Awatori Rentaro ARV-310) to prepare a curable composition.

[0108] Table 3 shows the contents (% by mass) of the thermally conductive fillers A, B and C in the total amount (100% by mass) of the thermally conductive filler (A).

[0109] The following evaluations were carried out using the curable compositions prepared in Examples 1 to 10 and Comparative Examples 1 to 6. The results are shown in Tables 1 and 2.

[0110] -evaluation- <Oil separation resistance> 200 g of the curable composition prepared above was sealed in a container (high resist container, product name: BHR-150, manufactured by Kinki Yoki Co., Ltd.) and stored at 10°C for 14 days, 28 days, or 60 days. After a specified number of days of storage, the liquid components that had separated from the curable compositions were removed, and the mass [g] was measured, and the oil separation resistance rate [%] was calculated based on the following formula A. (Formula A) Oil separation resistance rate [%] = (amount of oil-separated components [g] / amount of liquid components contained in the curable composition before storage [g]) × 100

[0111] In this evaluation, the curable composition was evaluated as having excellent oil separation resistance when the oil separation resistance rate [%] shown below was satisfied for each storage period. (Number of storage days) (Oil separation resistance rate [%]) 14 days 0.5% or less 28 days 1.0% or less 60 days 1.5% or less

[0112] <Viscosity> The shear viscosity η [Pa·s] of the curable composition prepared above at 25° C. was measured using a dynamic viscoelasticity measuring device (manufactured by Anton Paar, product name: MCR 101). A PP25 parallel plate (diameter 25 mm, manufactured by Anton Paar) was used as a jig for the curable composition to be measured. The measurements were performed by measuring the shear viscosity η [Pa s] at shear rates of 0.01 [1 / s], 0.1 [1 / s], 1 [1 / s], 10 [1 / s] and 100 [1 / s].

[0113] <Thermal conductivity [W / m K]> Thermal conductivity was measured according to ASTM D5470. The curable composition was molded to have dimensions of 10 mm x 10 mm x 1 mm (length x width x height (thickness)), sandwiched between 10 mm x 10 mm copper plates, and cured at 80°C for 30 minutes in a N2 purged atmosphere. The thermal resistance (unit: K cm) was then measured using a thermal resistance measuring device (Tsukubarika Seiki Co., Ltd., product name: thermal resistance measuring device). 2 / W) was measured and converted into thermal conductivity. In this evaluation, a material with a thermal conductivity of 3 W / m K or higher was considered to have excellent thermal conductivity.

[0114] <Spreading consistency> The spreading consistency was determined by inserting 0.05 mL of a sample (curable composition before curing) between two acrylic plates in an environment of 25°C, compressing the sample by applying a load of 100 g on the plates for 5 seconds, measuring the spreading diameter of the sample in millimeters, subtracting 1 from this measurement and multiplying the result by 20.

[0115] <Hardness: shape stability> -Softness after curing: Shore OO hardness (sample thickness: 6 mm)- The softness of the cured product of the curable composition was measured in accordance with ASTM D2240. The curable composition was molded into a size of 50 mm × 20 mm × 6 mm (thickness: 6 mm) and cured under a N2 purged atmosphere at 80°C for 30 minutes. The Shore OO hardness was then measured using a durometer (product name: GS-754G, manufactured by Techclock Corporation) and an Asker rubber hardness tester.

[0116] -Softness after hardening: Asker C hardness (sample thickness: 6 mm)- The softness of the cured product of the curable composition was measured in accordance with JIS K 7312:1996. The curable composition was molded into a size of 50 mm x 20 mm x 6 mm (thickness 6 mm) and cured under a N2 purged atmosphere at 80°C for 30 minutes, after which the Asker C hardness was measured using an Asker Rubber Hardness Tester Type C (manufactured by Kobunshi Keiki Co., Ltd.).

[0117] [Table 1]

[0118] [Table 2]

[0119] [Table 3]

[0120] Details of each component listed in Tables 1 and 2 are as follows. In Tables 1 and 2, "-" indicates that the corresponding component is not contained. In Tables 1 and 2, "filling ratio, [mass %]" represents the ratio of the total mass of the thermally conductive filler (A) to the total mass of the composition. In Table 3, "%" indicates "% by mass."

[0121] <<Monomer (B) Having a (Meth)acryloyl Group>> ITEC: 2-Decyltetradecyl methacrylate; manufactured by Shin-Nakamura Chemical Co., Ltd. Light Ester L: Lauryl methacrylate; Kyoeisha Chemical Co., Ltd., product name: LMA 9PG (bifunctional monomer): Polypropylene glycol dimethacrylate; manufactured by Shin-Nakamura Chemical Co., Ltd.; Product name: 9PG

[0122] <<Plasticizer (E)>> C-880: Adeka Cizer C-880 (product name); Trimellitic acid mixed linear alkyl ester; manufactured by ADEKA Corporation

[0123] <<Polymerization initiator (C)>> Perocta O: 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate; NOF Corp.

[0124] <<Dispersant (D)>> Oleic acid: Product name: Oleic acid, manufactured by Nippon Oil & Fats Co., Ltd.

[0125] <<Thermal conductive filler (A)>> (Zinc Oxide) Zinc oxide type 1: Volume average particle size: 0.6 μm, manufactured by Sakai Chemical Industry Co., Ltd. Calcined zinc oxide 1: Volume average particle size: 4 μm, manufactured by Hakusui Tech Co., Ltd. Calcined zinc oxide 2: Volume average particle size: 11 μm, manufactured by Hakusui Tech Co., Ltd. Calcined zinc oxide 3 (surface treatment product): treated with silane coupling agent, volume average particle size: 12 μm, manufactured by Hakusui Tech Co., Ltd. Calcined zinc oxide 4: Volume average particle size: 19 μm, manufactured by Hakusui Tech Co., Ltd. (Magnesium oxide) RF-10CS-SC: Product name, volume average particle size: 10 μm, manufactured by Ube Material Industries, Ltd. (Aluminum Oxide) AA-10: Product name:, Volume average particle size: 13.5 μm, manufactured by Sumitomo Chemical Co., Ltd.

[0126] As shown in the results in Tables 1 and 2, it is clear that the curable compositions of Examples 1 to 10 are superior to the curable compositions of Comparative Examples 1 to 6 in terms of oil separation resistance. From the above, the curable composition and cured product according to the present disclosure can be suitably used as a gap filler.

[0127] The disclosure of Japanese Patent Application No. 2021-061631, filed on March 31, 2021, is incorporated herein by reference in its entirety. All documents, patent applications, and technical standards described herein are incorporated herein by reference to the same extent as if each individual document, patent application, and technical standard was specifically and individually indicated to be incorporated by reference.

Claims

1. A thermally conductive filler (A) including a thermally conductive filler A having a volume average particle diameter of 0.3 μm or more and less than 1 μm, a thermally conductive filler B having a volume average particle diameter of 1 μm or more and less than 10 μm, and a thermally conductive filler C having a volume average particle diameter of 10 μm or more and 15 μm or less; A monomer (B) having a (meth)acryloyl group; A polymerization initiator (C); A dispersant (D), Based on the total mass of the thermally conductive filler (A), the content X of the thermally conductive filler A is 18.60% by mass to 40% by mass, the content Y of the thermally conductive filler B is 16.88% by mass to 40% by mass, and the content Z of the thermally conductive filler C is 20% by mass to 60% by mass. Curable composition.

2. The curable composition according to claim 1 , wherein the thermally conductive filler (A) comprises at least one selected from zinc oxide, magnesium oxide, and aluminum oxide.

3. The curable composition of claim 2 , wherein the thermally conductive filler (A) comprises zinc oxide.

4. The curable composition according to any one of claims 1 to 3, wherein the thermally conductive filler (A) is a surface-treated thermally conductive filler.

5. The curable composition according to any one of claims 1 to 4, wherein the monomer (B) comprises a compound represented by the following formula (1): 【Chemistry 1】 In formula (1), R 1 represents an alkyl group having 1 to 50 carbon atoms; R 2 represents a hydrogen atom or a methyl group.

6. The curable composition according to any one of claims 1 to 5, wherein the monomer (B) comprises a compound represented by the following formula (2): 【Chemistry 2】 In formula (2), R B1 represents an alkylene group having 1 to 5 carbon atoms; R B2 and R B3 each independently represents a hydrogen atom or a methyl group, and n represents an integer of 4 or greater.

7. A cured product of the curable composition according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Heat conductive pressure-sensitive adhesive composition, heat conductive pressure-sensitive adhesive sheet-shaped molded product, methods for producing them, and electronic equipment

    JP2016188297A

  • Maleimide resin film and composition for maleimide resin film

    JP2021038318A

  • Curable composition and cured material

    WO2020149193A1